Artificial Intelligence Implementation in Banks: A Systematic Literature Review and Future Research Directions - Kaoutar Tafali; Marouane Bejjaj; Taoufik Benkaraache (Journal of Information Systems Engineering and Business Intelligence, 2026)
Background: Implementation of artificial intelligence (AI) in banks becomes a necessity not only to gain competitiveness, but also to defend these financial institutions against emerging fintech firms. Many literature reviews related to AI implementation in banks have been conducted recently. Despite the fresh insights provided by the findings of these reviews, a comprehensive and complete study on AI adoption remains lacking, particularly a study that includes and synthesizes its antecedents, challenges, impacts, and success factors in banks. Objective: This study analyzes the antecedents, challenges, consequences, and guidelines related to AI implementation in banks. This study also seeks to identify the best practices recommended for policymakers and government authorities to support the adoption of this technology in the banking sector. Methods: A Systematic Literature Review using the Scopus and Web of Science databases, identified 42 relevant articles published between 2020 and May 2025. The research proposes a conceptual framework based on the IPO model, including antecedents, challenges, consequences and guidelines to deepen the understanding of AI implementation in banks and synthesize the current state of related knowledge. Results: The results revealed that the drivers and challenges are categorized into organizational, technological, and environmental topics based on the TOE and DOI theories, the consequences and guidelines provided to banks are categorized into organizational, technological, environmental, and people topics, and the guidelines provided to policymakers and government authorities are classified into AI governance, collaboration, and regulatory support topics.  Conclusion: This study provides both theoretical and practical contributions, by offering a comprehensive analysis of AI implementation in banks—a perspective that is lacking in the actual literature. It can also serve as a valuable guide for bank managers during the implementation process. In addition, the study proposes a research agenda for future research on AI implementation in banks.   Keywords: Artificial Intelligence, Banks, Financial sector, Banking sector, Input-Process-Output, Technology implementation